Increased dietary fiber is associated with weight loss among Full Plate Living program participants - Kelly, Rebecca K.; Calhoun, Janet; Hanus, Amy; Payne-Foster, Pamela; Stout, Ron; Sherman, Bruce W. (Frontiers in Nutrition, 2023)
Prior studies have demonstrated that an intake of foods rich in dietary fiber is associated with a favorable impact on health status and body weight. However, the association of fiber intake and weight loss has not been well studied in employer settings. The aim of this research was to assess the relationship of fiber and weight loss among individuals participating in the Full Plate Living (FPL) program. The 16-week plant predominant fiber-rich eating program was delivered to 72 employers, primarily in the Southwest U.S., over a three-year period (2017-2019). Participants received weekly video lessons, FPL materials, and additional online resources. A retrospective analysis of repeated measures was conducted using participant data obtained from 4,477 participants, of which 2,792 (62.5%) reduced body weight. Analysis of variance with post hoc analysis was used to assess the statistical significance of the changes between baseline and follow up measures of dietary fiber intake in each of the food categories, specifically the relationship of changes in individual and combined (composite) daily servings of fruits, vegetables, whole grains, beans, and nuts on body weight measures among three groups at follow-up: those who lost, maintained, or gained weight. Multilevel modeling was used to test the hypothesis that increased intake of fiber was associated with greater weight loss. Mean weight loss for the weight loss group was 3.28 kilograms. As compared to the other groups, the intake of whole fiber-rich foods at follow-up was significantly higher among the weight loss group with fruit (2.45 servings), vegetables (2.99 servings), beans (1.03 servings), and total fiber composite (9.07 servings) (P < .001). A significant increase in servings of grains was also noted (P < .05). Multilevel modeling demonstrated that a higher total fiber composite (Model 1), as well as higher intakes of either vegetables or fruits (Model 2) resulted in greater weight loss. Our findings indicate that the FPL program can be part of a lifestyle medicine approach to healthy eating and weight loss. Delivering the program in clinical, community and workplace settings can increase its reach as an effective and low-cost offering.